Meaning of Life for Retired Elderly in Salatiga City Nursing Home - Christina Widiastuti; Siswanto Siswanto (Proceedings of the 1st International Conference on Social Science (ICSS), 2025)
In a dimension of life, there are many phases passed and faced until the end of life. The elderly period is a phase of life where individuals begin to evaluate their life journey in every experience that has been passed. However, not all aged can easily find the meaning of life, especially those who live in nursing homes. This study aims to explore the description of the meaning of life in the elderly who live in nursing homes using a qualitative approach method with descriptive phenomenology research type. Data were collected through interviews and observations of three elderly individuals who have lived in a nursing home for more than one year. The individuals are able to communicate effectively, maintain good health, and are free from significant health problems such as dementia or psychotic disorders. The data collected was then analyzed using phenomenological analysis using Giorgi's five stages. The results showed that there were variations in the experience of finding the meaning of life; participants M and A showed success in achieving the meaning of life through meaning of life, self-commitment, directed activities and social support, so that participants M and A feel happy and have positive social relationships. On the other hand, participant M does not succeed in finding the meaning of life and experiences life in the orphanage as suffering, characterized by feelings of alienation, disconnection, and loneliness. This study used a small sample size (only 3), and perhaps the findings cannot be generalized, but these findings are expected to provide an overview of the meaning of life in elderly retirees living in a nursing home, and can contribute to the development of psychology, especially topics related to the meaning of life. A suggestion for the future: the researcher can examine how social support in nursing home relates to increasing the meaningfulness of life for the elderly.